If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -2) = -3 Reorder the terms: -2(-2 + x) = -3 (-2 * -2 + x * -2) = -3 (4 + -2x) = -3 Solving 4 + -2x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -2x = -3 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = -3 + -4 -2x = -3 + -4 Combine like terms: -3 + -4 = -7 -2x = -7 Divide each side by '-2'. x = 3.5 Simplifying x = 3.5
| 8x-13+4x+1+6x-6=180 | | -5(a+2)+5=-7(5-a)-6 | | 9(x)+8=90 | | 16=10-(-4x+2) | | 7v(z-2v)=12 | | 11-2g=3 | | -5X/6=-X-1/2 | | 20y+5=4+5y | | -6x+2(2x-15)=-6 | | -3(-2x+5)=17 | | -1.2=13x-18 | | 2y+12=66 | | z^2+14z=-45 | | X*240=12 | | 6=35 | | -6x-3(-3x+17)=-36 | | (5s+6)(s-2)= | | -7(4-4x)=-168 | | 8(t-2)+6t=7(2t+3)-9 | | -6(-7x-1)-x=-158 | | 7n-15=-16+8n | | -4x-6(-2x+15)=-10 | | 1/2(4/3)(3.14)(2.5)^3 | | -2x-3=2x+9 | | 4(6n-7)=140 | | 3(x-1)=7+5 | | n^2+9=34 | | Y=29(3)x | | 4(6n-7)=40 | | Y=29(3) | | 2/3x12/11 | | (n-6)(n-4)= |